In vitro study of aqueous and methanol extracts of Tinospora Crispa (L.) Hook. F. & Thomson in early stage atherogenesis - Kamarazaman, Ihsan Safwan (2012)
Tinospora crispa, locally known as ‘Patawali’ in Malaysia, is a plant belonging to the family of Menispermaceae. It is a climber that can be found in primary rainforest widely distributed in Malaysia, Indonesia, Thailand and Vietnam. T. crispa has been traditionally used to treat diabetes, hypertension and lumbago and reported to have antidiabetic, hypotensive and anti-inflammatory activity. The aimed of this study was to investigate the antioxidant properties of this plant as well as its ability to attenuate the release of oxidant and inflammatory markers in induced oxidation and inflammation in human umbilical vein cells (HUVECs). In vitro studies have been conducted to evaluate antioxidant properties of T. crispa. The radical scavenging activity was tested by 1,1-diphenyl-2-picrylhydraxyl (DPPH) assay. The result showed DPPH scavenging activity of T. crispa aqueous (TCAE) and methanol extract (TCME) were 82 ± 1.78 and 73 ± 1.01%, respectively. The ability of T. crispa extracts to reduce Fe3+ to Fe2+ were tested by FRAP assay and the result showed FRAP value of TCAE and TCME were 1.04 ± 0.27 and 1.64 ± 0.06 mmol/L, respectively. Total flavonoids content (TFC) and total phenolics content (TPC) were also measured. The result showed TFC value of TCAE and TCME were 205.58 ± 3.5 and 223 ± 10.49 mg QE/g sample, respectively while TPC value of TCAE and TCME were 32.58 ± 0.68 and 41.64 ± 0.97 mg GAE/mg sample, respectively. The antioxidant enzymes activities and the level of anti-inflammatory markers in HUVECs treated with TCAE and TCME to counter the oxidative effect by hydrogen peroxide (H2O2) or inflammatory effect by tumor necrosis factor- α (TNF-α) were also measured. HUVECs were seeded at 1 x 106 cell/well in 6-well plate and the treatments were divided into 3 groups; normal control, negative control, and treated groups. In the negative control (NC) group, HUVECs were exposed to either 250 μM H2O2 or 10 ng/mL TNF-α alone, whereas in the treated groups HUVECs were pretreated with various concentrations of TCAE and TCME (100, 200, 400 and 600 μg/mL) for 30 minutes prior to exposure to H2O2 (250 μM) or TNF-α (10 ng/mL). In the normal control groups, HUVECs were incubated with culture medium only. The cells were incubated for 24 hours at 37 oC with 5% CO2 supply for further analysis. Assays that were performed in present study were antioxidant enzyme activities such as catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx), lipid peroxidation level by malondealdehyde (MDA) assay, and inflammatory markers such as nitric oxide (NO), intercellular cell adhesion molecule (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), monocyte chemotactic protein-1 (MCP-1) and macrophage colony stimulating factor (M-CSF). Results of antioxidant enzymes activity assays (CAT, SOD and GPx) showed TCAE and TCME at a concentration ranges from 100-600 μg/ml significantly increased (p<0.05) the level of those antioxidant enzymes compared to NC. Results of MDA assay showed significant reduction (p<0.05) of MDA level in HUVECs treated with TCAE and TCME compared to NC. Concomitantly, the level of NO expression in HUVECs treated with TCAE and TCME was significantly elevated (p<0.05) compared to NC. In addition, inflammatory markers assays showed TCAE and TCME have significantly reduced (p<0.05, 0.01) the secretion of ICAM-1, VCAM-1 and M-CSF as compared to NC. However, secretion of MCP-1 was not reduced by the treatment of TCAE and TCME. Taken together, this study suggest that TCAE and TCME can effectively prevent oxidative stress by H2O2 and inflammation by TNF-α on HUVECs, which might be importance in the treatment of atherosclerosis.